Using Unified Theory of Acceptance and Use of Technology to Evaluate the Impact of a Mobile Payment App on the Shopping Intention and Usage Behavior of Middle-Aged Customers - Liu, Che-Hung; Chen, Yen-Tzu; Kittikowit, Santhaya; Hongsuchon, Tanaporn; Chen, Yi-Jing (Frontiers in Psychology, 2022)
This research adopted the unified theory of acceptance and use of technology (UTAUT) to emphasize the use of the PX Pay mobile payment app for PX Mart, the most popular supermarket in Taiwan, and examine the degree of involvement as a moderator. The influence of factors related to PX Mart’s target customer groups on their shopping intentions and usage behaviors were discussed, with subsequent benefits and optimization directions. This study indicated the following results. First, performance expectations, ease-of-use expectations, and social impact enhance consumers' behavioral intention and behavioral intention significantly influence usage behavior. Second, gender has no significant moderating effect on the proposed model. Third, age has a moderating effect from performance expectations and ease-of-use expectations, social influence on behavioral intention. Fourth, use is more significantly affected by perceived stakeholders for customers over age 50 than for those age 30-39. Fifth, the degree of involvement significantly affects the relationship between behavioral intention and usage behavior in terms of social influence and facilitating conditions effects. Finally, we provided academic and practical implications and make contributions to both the online payment industry and academia.